Macroeconomic Determinants of Under-Five Mortality Rate in Nigeria - Kehinde Kabir Agbatogun; Opeloyeru Olaide Sekinat (Signifikan: Jurnal Ilmu Ekonomi, 2020)
This paper examined the macroeconomic determinants of under-five mortality rate in Nigeria between 1980 and 2017. The study was predicated on the Grossman analytical framework rooted in the human capital development theory. A macro-econometric model incorporating major macroeconomic variables in explaining under-five mortality health outcomes. ARDL bound test estimation technique that took into consideration error correction mechanism was used. Tests of the model’s reliability were carried out using unit root and co-integration tests. The influences of government health expenditure was significant, however both immunisation initiatives and health workers exerted an insignificant positive influence on under-five mortality rate. Thus, the study recommends policies targeted to improve Nigeria health system both in terms of creation of awareness relating to the service delivery and human capital development of the professionals in the sector to avert brain drain syndrome in the country.JEL Classification: J11, J13 How to Cite:Agbatogun, K. K., & Opeloyeru, O. K. (2020). Macroeconomic Determinants of Under-Five Mortality Rate in Nigeria. Signifikan: Jurnal Ilmu Ekonomi, 9(2), 177-186. https://doi.org/10.15408/sjie.v9i2.13751.